Review of the Effects of the Abuse of Narcotics, Psychotropics, and Other Addictive Substances - Samsul, Erwin; Amiruddin, Widya Salsabila Putri; Hasanah, Fitri; Wulandari, Tiara Sahfitri; Basongan, Oktariani; Syam, Mawar Inrian; Yusuf, Muhammad; Gala, Kretentia Aprilia; Rachmawati, Nova Sri (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2025)
The purpose of this study was to identify the forms of drug abuse and evaluate the impact of drug abuse in the community. This research uses a qualitative approach and is a descriptive study. This research uses the narrative literature method. This review process used the narrative review method by collecting literature from various sources, including scientific journals, government reports, and relevant conference articles, with the inclusion criteria being articles published within the last 10 years, in Indonesian or English, and discussing topics related to the impact or intervention of drug abuse. In the initial stage of searching journal articles, 17,083 articles from 2019-2024 with identified keywords such as